Effect of mode order, resonator length, curvature, and electrode coverage on enhancing the performance of biconvex resonators. (1st June 2018) - Siddiqi, Muhammad Wajih Ullah; Tu, Cheng; Lee, Joshua E-Y
Abstract: Previous work has demonstrated the effectiveness of the biconvex approach in enhancing the quality factor of piezoelectric resonators. This paper explores biconvex resonators in more detail. The first of these considerations include modifying the resonator geometry when extending the mode order to reduce the motional series resistance. Results for applying various curvatures are described to illustrate the effect of resonator length in providing the possibility to reliably enhance quality factor through an optimal range of curvatures. The drawbacks of over-curving biconvex resonators are also elucidated herein. This paper further describes the effect of the electrode geometry (by varying the area coverage and the number of interdigitated transducer electrodes) in the limit where anchor losses in the biconvex resonators have been reduced to the point such that electrode-related losses have a measurable effect.